2017
DOI: 10.1097/fpc.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

Quality of anticoagulation control and hemorrhage risk among African American and European American warfarin users

Abstract: Objective We evaluated whether PTTR, risk of over-anticoagulation (INR>4) and risk of hemorrhage differs by race. As PTTR is a strong predictor of hemorrhage risk, we also determined the influence of PTTR on risk of hemorrhage by race. Methods Among 1326 warfarin users, PTTR was calculated as the percentage of interpolated INR values within the target range of 2.0–3.0. PTTR was also categorized as poor (PTTR <60%), good (PTTR≥60<70%), or excellent (PTTR≥70%) anticoagulation control. Over-anticoagulation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…We also evaluated the differential effect of self-reported race on warfarin, reporting on the variable effect of genetic and nongenetic factors on warfarin dose and hemorrhage by race. 28,36 However, the effect of age on warfarin dose was similar across race groups in our study. 28 Age is also an important predictor of bleeding outcomes among warfarin users and has been incorporated into several bleeding risk scores.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…We also evaluated the differential effect of self-reported race on warfarin, reporting on the variable effect of genetic and nongenetic factors on warfarin dose and hemorrhage by race. 28,36 However, the effect of age on warfarin dose was similar across race groups in our study. 28 Age is also an important predictor of bleeding outcomes among warfarin users and has been incorporated into several bleeding risk scores.…”
Section: Discussionsupporting
confidence: 53%
“…Our own research group has previously reported on the associations of kidney function, left ventricular systolic dysfunction, and the CYP2C9 , VKORC1 , and CYP4F2 variants with warfarin dose. We also evaluated the differential effect of self‐reported race on warfarin, reporting on the variable effect of genetic and nongenetic factors on warfarin dose and hemorrhage by race . However, the effect of age on warfarin dose was similar across race groups in our study …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, they experienced significantly lower bleeding episodes (Incidence rate ratio: 1.38, 95% CI: 1.01, 1.89, P = .045) and were at significantly lower relative risk of major hemorrhagic events (HR: 1.58; 95% CI: 1.04-2.41; P = .03) despite adjusting for clinical and genetic factors and TTR. 30 In the study of Kataruka et al, 21 none of the score’s factors was independently associated with predicting poor anticoagulation control. Analysis identified weight, history of previous VTE, and alcohol consumption, which are risk factors not included in the SAMe-TT 2 R 2 score, as significant predictors of low TTR (<60%).…”
Section: Discussionmentioning
confidence: 96%